Unraveling the Structure and Function of Melanin through Synthesis - Cao, Wei; Zhou, Xuhao; McCallum, Naneki C; Hu, Ziying; Ni, Qing Zhe; Kapoor, Utkarsh; Heil, Christian M; Cay, Kristine S; Zand, Tara; Mantanona, Alex J; Jayaraman, Arthi; Dhinojwala, Ali; et al. (Journal of the American Chemical Society, 2021)
Melanin is ubiquitous in living organisms across different biological kingdoms of life, making it an important, natural biomaterial. Its presence in nature from microorganisms to higher animals and plants is attributed to the many functions of melanin, including pigmentation, radical scavenging, radiation protection, and thermal regulation. Generally, melanin is classified into five types-eumelanin, pheomelanin, neuromelanin, allomelanin, and pyomelanin-based on the various chemical precursors used in their biosynthesis. Despite its long history of study, the exact chemical makeup of melanin remains unclear, and it moreover has an inherent diversity and complexity of chemical structure, likely including many functions and properties that remain to be identified. Synthetic mimics have begun to play a broader role in unraveling structure and function relationships of natural melanins. In the past decade, polydopamine, which has served as the conventional form of synthetic eumelanin, has dominated the literature on melanin-based materials, while the synthetic analogues of other melanins have received far less attention. In this perspective, we will discuss the synthesis of melanin materials with a special focus beyond polydopamine. We will emphasize efforts to elucidate biosynthetic pathways and structural characterization approaches that can be harnessed to interrogate specific structure-function relationships, including electron paramagnetic resonance (EPR) and solid-state nuclear magnetic resonance (ssNMR) spectroscopy. We believe that this timely Perspective will introduce this class of biopolymer to the broader chemistry community, where we hope to stimulate new opportunities in novel, melanin-based poly-functional synthetic materials.